Cetaceans and mass strandings in Thai waters - Adulyanukosol, Kanjana; Thaongsukdee, Surasak; Kittiwattanawong, Kongkiat (J. Cetacean Res. Manage., 2023)
A total of 25 species of cetaceans have been recorded in Thai waters from stranding and sighting records. A summary of these, together with details of five mass strandings on the Andaman Sea coast of Thailand, are reported here. The first mass stranding, of nine spinner dolphins (Stenella longirostris) was at Talibong Island, Trang Province, in January 1999; six carcasses were examined and three were lost. The second record comprised five spotted dolphins (Stenella attenuata) stranded at Ban Ko Kho Khao, Phang-nga, in February 1999; two dolphins were released alive. The third stranding was of eight spotted dolphins at Mai Phai Island, Phang-nga, in March 2006; five animals died and three were released alive. The fourth mass stranding was of 30 false killer whales (Pseudorca crassidens) at Racha Yai Island, Phuket, in June 2008; 29 animals were released while one drowned. The fifth record consisted of three rough-toothed dolphins (Steno bredanensis) stranded at Nam Bor Bay, Phuket, in July 2008; all three were returned to the open sea. It was difficult to determine the causes of death of the stranded dolphins. However, it was possible that the first two mass strandings were caused by disease. Some strandings were possibly influenced by the landscape of the stranding locations (narrow bay in one case, wide gently sloping beach in another).